Technology Acceptance Model : Intention Implementation E-Goverment System - Iswahyudi, M (AKRUAL: JURNAL AKUNTANSI, 2022)
This study aimed to examine the influence of perceived usefulness and perceived ease of use on individual attitudes and intentions to use the E-Government System (EGS), with gender as a moderating variable. The EGS in question refers to systems utilized by government agencies in Banyuwangi, such as e-village budgeting, e-monitoring, and simral. The research employed a survey method using questionnaires, with EGS operators from each agency serving as the sample. Data analysis was conducted using Partial Least Squares (PLS) with WarpPLS version 3.0 software. The results indicated that perceived usefulness played a significant role as a determinant of individuals' attitudes and intentions to use the EGS, where the users' attitudes, in turn, influenced their interest in using the system. The study also found that perceived ease of use did not have an impact on individuals' attitudes toward using the EGS. Moreover, gender was found not to moderate the relationship between perceived ease of use and perceived usefulness with individual attitudes toward using the EGS. This suggests that psychological factors such as perceived usefulness and ease of use have a more substantial influence on EGS usage than demographic factors like gender among government agency operators in Banyuwangi.